WORK-LIFE BALANCE AND EMPLOYEE OUTCOMES: A MULTICULTURAL STUDY IN GHANA - Emilia , Bianchi (Journal of Allied Research in Management and Entrepreneurship (JARME), 2024)
This study investigates how work-life balance practices impact employee outcomes such as job satisfaction, productivity, and well-being in multicultural work environments in Ghana. A crosssectional study was conducted using an online survey of 336 participants from diverse cultural backgrounds across four regions in Ghana. The findings indicate that factors such as leadership support, flexible policies, fair compensation, training opportunities, and organizational culture significantly influence work-life balance, employee performance, and retention. Additionally, age, gender, income level, and marital status moderate this relationship. The results highlight the need for inclusive policies tailored to the unique needs of different demographic groups to enhance work-life balance. Fostering diversity, equity, and flexibility is ethically upright and strategically imperative for organizational success through improved employee outcomes. This study contributes empirical insights on managing work-life balance effectively across cultural contexts, aiding multinational organizations in supporting a global workforce